Osman Bölükbaşı’nın siyasi faaliyetleri (1913-2002) - Ayhan, Evren (My University, 2006)
Osman BÖLÜKBAŞI, 1913 yılında Kırşehir'de dünyaya geldi, Fransa'da Nancy Üniversitesinin matematik ve astronomi bölümünü bitirdi I946'da çok partili hayatın başlamasıyla Demokrat Partiye katıldı. Bir yıl sonra Demokrat Parti’den ayrılarak Millet Partisi'nin kuruluşunda yer aldı. 1950 yılında Kırşehir Milletvekili seçilen Bölükbaşı, Millet Partisi’nin kapatılmasıyla Cumhuriyetçi Millet Partisi’nin kurucuları arasında yer aldı, 1954’te Demokrat Parti ile olan çatışmasından dolayı Kırşehir ilçe yapıldı, 1955 yılında Cumhuriyetçi Millet Partisi Genel Başkan’ı oldu. Bölükbaşı, 1946'da başladığı siyasî yaşamı içerisinde 1950, 1954, 1957 seçimlerinde Kırşehir Milletvekili 1961, 1965, 1969 seçimlerinde de Ankara milletvekili seçilmiştir.Sert konuşmaları ve farklı siyasî üslubu ile Türk siyasetinin önemli isimlerinden biri olarak yerini almıştır. 1961 yılında İnönü Başkanlığındaki koalisyona girmek istemeyen Bölükbaşı ile bir grup milletvekili Cumhuriyetçi Köylü Millet Partisi’nden istifa ederek ikinci defa Millet Partisi’ni kurdu. 1972 yılında Genel Başkanlık görevinden, 1973 yılında da; milletvekilliğinden ve partisinden ayrılarak siyaseti bırakan Bölükbaşı, 6 Şubat 2002'de Ankara’da vefat etti.

Osman Bolukbasi was born in 1913 in Kirsehir. He studied mathematics and astronomy at the Nancy University in France. In 1946 , so multi party system begun he attended to the Democrat Party. A year later , he left the Democrat Party then he attended to the Folk Party’s foundation. In 1950, he was elected as a Kirsehir deputy. So Folk Party was closed, he took place in The Republic Folk Party’s founders. So he didn’t go well with the Democrat Party in 1954, Kirsehir was been country. In 1955 he became leader of the Republic Folk Party. Bolukbasi started his political life in 1946, then he was elected as a Kirsehir deputy in 1950,1954,1957 elections. After that he was elected as a Ankara deputy in 1961,1965,1969 elections. He was a milestone in Turkish politicians with different talking and different political idea. In 1961, so he didn’t want to be in coalition with Inonu , Bolukbasi and a group of the Republic Villager Folk Party resigned from the Republic Villager Folk Party. Then they founded the Folk Party. In 1972, he resigned from his chairmanship function. In 1973,he resigned from his deputy function and his party. Bolukbasi died in Ankara on 6th February in 2002.
Keywords: Biyografi_Osman Bölükbaşı; Osman Bölükbaşı_Siyaset_1913-2002